The effect of special exercises using weights in developing some of the physical abilities of the limbs and the accuracy of performing the skill of wavy transmission in volleyball - Latif Ghaida, Fouad Abdel; Abbas Zidan, Khaled; Abbas Zidan, Intisar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to prepare special exercises using weights in developing some of the physical abilities of the limbs and the accuracy of performing the skill of the wavy transmission in volleyball for the members of the research sample, as well as to identify the effect of special exercises using weights in developing some of the physical abilities of the limbs and the accuracy of performing the skill of the wavy transmission in volleyball for the sample members The research, as the researchers used the experimental method for its suitability to solve the research problem, and the design of the two equal groups with pre and post tests was chosen randomly, as training with weights is one of the effective training methods that lead to the development of muscular strength in its various forms, and training with weights is one of the important parts that are Within the coach’s exercises, the use of weights has increased as a kind of change in the training methods that lead to improving the level of the athlete, as the research sample consisted of players from the University of Diyala team and by (10) players out of (15) players, and through the lottery, they were randomly divided into two experimental and control groups, each group (5) players, as numbers were drawn from (1-10), so numbers (1-5) represented the experimental group and numbers ( 6-10) The control group was represented, in addition to the use of appropriate means, tools and devices, the exploratory experiment was conducted, as well as the pre-tests for the two groups, the application of special exercises, and the post-tests for the two groups, after which the data was unloaded and statistically processed, and then presented, analyzed and discussed The researchers reached several conclusions, which are : 1. The exercises for the use of weights prepared by the researchers contributed significantly to the development of some of the physical abilities of the limbs and the accuracy of the performance of the wavy transmission skill among the members of the experimental group. 2. The gradation in the training load and the diversity in the special exercises for using weights prepared by the researchers had a positive effect in developing some of the physical abilities of the limbs and the accuracy of the performance of the wavy transmission skill among the members of the experimental group . 3. The experimental group had an advantage compared to the control group in developing some of the physical abilities of the limbs and the accuracy of performing the wavy transmission skill among the members of the research sample . The researchers reached several recommendations : 1. The use of exercises for the use of weights prepared by researchers in the training of volleyball teams to achieve better sporting achievements . 2. The use of tests used in research in the training process. 3. Conducting similar research on age groups and other physical and skill variables.